SARS-CoV-2 PCR and antibody positivity among school staff at the beginning and end of the first school term - Moza Alishaq (BMC, 2021)
Abstract Background There is controversy regarding the role of in-person attendance in schools and transmission of the SARS-CoV-2 pandemic. Several studies have demonstrated no increase in transmission, while some have reported large outbreaks with in-person attendance. We determined the incidence and risk factors for SARS-CoV-2 infection among school staff after one school term. Methods Nasopharyngeal swabs (NPS) for SARS-CoV-2 RT-PCR and blood for SARS-CoV-2 antibody testing were obtained from staff at a large international school in Qatar at the beginning of the 2020–2021 school year and repeated at the end of the first term. Results A total of 376 staff provided samples for testing. At the beginning of the 2020–2021 school year, the PCR positivity for SARS-CoV-2 was 13%, while seropositivity was 30.1%. A majority of those who tested positive either by PCR or serologically, were non-teaching staff. At the end of the first school term four months later, only 3.5% of the initially antibody-negative staff had seroconverted. In multivariable logistic regression analysis, male gender (OR 11.48, 95%CI 4.77–27.64), non-teaching job category (OR 3.09, 95%CI 1.10–8.64), contact with a confirmed case (OR 20.81, 95%CI 2.90–149.18), and presence of symptoms in the preceding 2 weeks [1–2 symptoms OR 4.82, 95%CI 1.79–12.94); ≥3 symptoms OR 42.30, 95%CI 3.76–476.43) independently predicted SARS-CoV-2 infection in school staff before school starting. Conclusion Male gender, non-teaching job, presence of symptoms, and exposure to a confirmed case were associated with higher risk of infection. These data can help policymakers in determining the optimal strategy for school reopening.